Body weight perception by college going adolescents of North Karnataka, India- A cross sectional study - Banjade, B; Naik, VA; Narasannavar, AB (Nepal Journal of Medical Sciences, 2015)
Background: Adolescence (10-19 year) is a period of transition from childhood to adulthood. The factor that determines how adolescents feel about themselves is ‘Body image’. The objective of study is to understand body weight perception of adolescents. Methods: This cross-sectional study was conducted in the two Pre- University colleges with a sample of 330 adolescents. Pre-designed and pre-tested questionnaire was used to elicit the required information. Results: 13 % of study participants underestimated their body weight and 11.2 % over estimated their body weight. 82.7% of study subjects perceived themselves as normal weight for their age and height, 7.6% perceived as underweight and 9.7% perceived as overweight/obese. Conclusion: Inappropriate perceptions about body weight leads to increase in the problems related to overweight/obesity. Lack of knowledge about and access to growth charts has probably made difficult for adolescents to evaluate their weight status objectively. So, college can play an effective role to help them to know actual body weight Nepal Journal of Medical Sciences Vol.3(2) 2014: 106-109